Cholesterol-lowering and anti-atherogenic properties of edible bird’s nest in vitro and in vivo - Mohamad Nasir, Nurul Nadiah (2022)
Edible bird’s nest (EBN) is a highly nutritious food product with proven cardioprotective effects. However, the fundamental mechanisms involved in preventing atherogenesis remain unknown, particularly those related to cholesterol metabolism and atherosclerotic plaque formation. The present study concentrates on the cholesterol-lowering and anti-atherogenic properties of EBN, using both in vitro and in vivo models. Two different shapes of EBNs were used in this study, namely half-cup (HC) and stripe-shaped (ST). Major nutrients in EBNs are protein (54-57%), carbohydrates (22-24%), crude fibre (3-20%), calcium (650-740 mg/100g), sodium (500-680 mg/100g), and magnesium (100-130 mg/100g). Both essential and non-essential amino acids were also identified in the EBNs from this study. Full stew (FS) and stew extract (SE) from HC of EBN were selected for the next analyses as it showed high extraction yield (FS: 92.29 ± 2.45%; SE: 12.50 ± 0.89%) and soluble protein concentration (FS: 375.6 ± 0.98 μg/mL; SE: 435.6 ± 2.63 μg/mL) as compared to the ST of EBN (p < 0.05). HPLC analysis showed that bioactive sialic acid was detected in both FS (7.91%) and SE (8.47%) of HC EBN, and was confirmed by SDS-PAGE. In this study, a novel protein marker, namely 78-kDa glucose-regulated protein was discovered in FS and SE of HC EBN by using LC-MS/MS. Digested HC EBN (FSh: FS hydrolysate; SEh: SE hydrolysate) possesses high activity as an antioxidant, anti-inflammatory, and inhibitor of HMGCR as compared to unhydrolyzed HC EBN. In vitro results demonstrated the potency of FSh and SEh in reducing inflammatory mediator secretion (NO: 42-60%; IL-6: 56-63%; IL-1β: 34-60%), monocyte migration (24-33%), and macrophage-cholesterol accumulation (40.4-42.9%) with more than 80% of cell viability in RAW 264.7 macrophages and THP-1 monocytes. Further in vivo investigation highlighted that dietary intervention with FS or SE of HC EBN at 500 mg/kg b.w/day for 12 weeks significantly improved serum lipid profiles (i.e., reduced TC: 6.8-11.5%, LDL-c: 9.1-20.6%, TG: 42.4-44.2%, and increased HDL-c: 39.5%), atherogenic indices (i.e., reduced CRI-I: 21.2-22.8%, CRI-II: 22.8-35.5%, AI: 19.4-33.4%), hepatosteatosis, stabilization of atherosclerotic plaque (i.e., reduced I/M ratio: 27.3-43.6%), coagulation status (i.e., increased PT: 30-34%, APTT: 16-19%, and reduced Fb: 40-60%), liver function (i.e., reduced serum ALT: 28-30%, GGT: 26-29%), systemic oxidant-antioxidant balance (i.e., increased serum TAC: 39-48%, SOD: 135-295%, CAT: 27-29%, and reduced serum oxLDL: 20-34%), and inflammatory response (i.e., reduced serum P-selectin: 18-23%, MCP-1: 54-66%, IL-6: 40-47%, IL-1β: 32-49%) in the hypercholesterolemic rabbits (p < 0.05). EBNs supplementation also lowered the levels of hepatic HMGCR (1.3-1.4 fold), hepatic TC (1.6-1.7 fold) and aortic TC (1.9-2.2 fold) (p < 0.05). The modulatory effects of EBN on key genes related to cholesterol metabolism in the liver and aorta tissues showed consistent transcript regulation of PPARγ, LXRα, ABCA1, and LCAT. Gene expression analysis also suggested the potential involvement of the NOS3/NF-ĸB pathway in alleviating vascular oxidative stress and inflammation in hypercholesterolemic rabbits. This study provides scientific evidence and proves that consumption of EBN lowers cholesterol levels and could prevent atherogenesis. Therefore, it has a high potential therapeutic target in the prevention of atherosclerosis.